Management of hearing loss in children. Issue 1 (January 2016) - Gan, Richard; Rowe, Aimee; Benton, Claire; Daniel, Matija
Abstract: As hearing is crucial in the development and well-being of children it is important for clinicians to be up to date with the management options for hearing loss in children. Current options include hearing aids, surgery such as ventilation tubes or cochlear implants, or conservative management. All management strategies are most successfully carried out as a team effort involving the child, parent, school and multidisciplinary team. This article outlines each of these options in detail according to conditions causing conductive or sensorineural hearing loss.